Sustainable energy adoption in UAE homes (villas and apartments) - Salameh, Muna; Touqan, Basim (Frontiers in Built Environment, 2026)
IntroductionGlobal warming is a major 21st-century challenge, requiring a shift toward sustainable lifestyles—especially in how homes are designed and powered. This study investigates the factors shaping household adoption of residential solar (renewable energy) in the UAE, where buildings (including housing) account for nearly 80% of total electricity consumption. Understanding what drives UAE residents to adopt renewable energy at home is essential for accelerating sustainable housing and supporting climate-change mitigation.MethodsA quantitative, cross-sectional survey was conducted using a structured questionnaire targeting UAE households. Data were analyzed using factor analysis in SPSS. The initially calculated sample size was 73; of 90 respondents, 82 valid responses were included in the final analysis.ResultsThe findings show that economic benefits are the strongest motivator for adopting renewable energy in residential settings. The study provides a quantified ranking of adoption motivators: economic benefit (∼41.8%) as the primary factor, followed by government role (∼17%), and climate-risk awareness (∼6.4%). Overall, four extracted factors explain approximately 82.4% of the total variance.DiscussionThe study’s key contribution is the quantified ranking and relative weight of household adoption drivers in the UAE—an evidence granularity that is not commonly reported in prior UAE research. These results provide actionable direction for policymakers and practitioners: strengthening financial attractiveness and enabling government mechanisms appears most influential, while awareness-related drivers play a smaller (but still relevant) role. The findings also indicate that additional determinants likely exist beyond the extracted factors, supporting further research to identify other barriers and enablers for wider deployment of renewable energy solutions across UAE housing types (villas and apartments).